From Substance Abuse to Unsafe Sexual Behavior at an Early Age: Maladies of Street Children of Kathmandu City, Nepal - Thapa, Man Bahadur; Pandey, Rishikesh (Quest Journal of Management and Social Sciences, 2023)
Background: Street children are a marginalized group considered the most at-risk population (MARPs). Because of their substance abuse practice, ranging from glue sniffing to injecting drugs and unsafe sexual behavior, they are vulnerable to transmitting HIV and other blood-borne diseases. Numerous studies have been conducted on street children in Kathmandu. However, there are gaps in studying hardcore substance abuse and unsafe sexual behavior. Objective: This study aims to assess the state of substance abuse and practice of unsafe sexual behavior among the street children of Kathmandu city. Methods: This research applied both exploratory and descriptive study designs. Using the non-probability sampling of snowball sampling technique, we interviewed 50 respondents (including six females) from purposively selected three location clusters, i.e., New-road, Thamel and Gaushala/ Pashupati Temple area of Kathmandu)have been interviewed. We used both open-ended and close-ended questions to collect data. Results: The findings of the study disclosed that substance abuse transitioned from solvent use in the earlier ages of 11 to 13 years to the progress towards injecting drugs as they grow older, 14 to 16 years old. Of the total, 14% of the respondents sharing the needle/syringe with others while injecting drugs. Likewise, 88% of the male respondents have reported practicing unsafe sexual behavior, with their friends, in exchange for food and money. Conclusion: The street children of Kathmandu are living a risky life. Substance abuse and unsafe sexual activities are the most high-risk behavior, making them vulnerable to transmission of HIV, HCV, HBV and STIs. However, the policies to respond to the issue of street children in Nepal are simply inadequate and ineffective.